Standing on the shoulders of science - Martin Watzinger; Monika Schnitzer (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
The goal of science is to advance knowledge, yet little is known about its value for marketplace inventions. While important breakthrough technologies could not have been developed without scientific background, skeptics argue that this is the exception rather than the rule, questioning the usefulness of basic research for private sector innovations and the effectiveness of the knowledge transfer from university to industry. We analyze the universe of U.S. patents to establish three new facts about the relationship between science and the value of inventions. First, we show that a patent that directly builds on science is on average 2.9 million U.S. dollars more valuable than a patent in the same technology that is unrelated to science. Based on the analysis of the patent text, we show second that the novelty of patents predicts their value, and third that science-intensive patents are more novel. This documents that science introduces new concepts that are valuable for marketplace inventions. Our study informs the debate on the merits of science for corporate innovation and the origins of breakthrough inventions.
Keywords: O30; O34; O33; O31; 330